Bank bonuses and bail-outs - Hendrik Hakenes; Isabel Schnabel (Max Planck Institute for Research on Collective Goods, 2013)
This paper shows that bonus contracts may arise endogenously as a response to agency problems within banks, and analyzes how compensation schemes change in reaction to anticipated bail-outs. If there is a risk-shifting problem, bail-out expectations lead to steeper bonus schemes and even more risk-taking. If there is an effort problem, the compensation scheme becomes flatter and effort decreases. If both types of agency problems are present, a sufficiently large increase in bailout perceptions makes it optimal for a welfare-maximizing regulator to impose caps on bank bonuses. In contrast, raising managers' liability can be counterproductive.
Keywords: J33; G21; G28; M52; 330; bonus payments; bank bail-outs; bank management compensation; risk-shifting; underinvestment; limited and unlimited liability